Thinking through the image the visual events of Miroslav Petříček - Hlaváčková, Jitka; Bartlová, Milena 1958-; Janoščík, Václav; Petříček, Miroslav 1951-; Přibáň, Jiří 1967- (Prague City Gallery, 2023)
Miroslav Petříček is a leading Czech philosopher and aesthetician who has been systematically reflecting on visual art for decades. He has summarised his thoughts on aspects of the language of art in a number of texts, including his book Thinking through Images, which became the main stimulus for this exhibition. Our most important aim is to highlight Miroslav Petříček’s fundamental contribution to the development of Czech visual art and to attempt to illustrate the key ideas underlying his philosophical discourse. The basis is his statement that an encounter with an image is an event
Published on the occasion of the exhibition "Thinking Through the Image: The Visual Events of Miroslav Petříček", held from 4 October 2023 to 28 January 2024 at Prague City Gallery - Municipal Library, 2nd floor
Print run: 200
Keywords: Petříček, Miroslav -- 1951-; Geschichte 1971-2023; Kunst; Ästhetik; Tschechien; Tschechoslowakei; české výtvarné umění / 20.-21. století; teorie umění; filozofie umění; Czech art / 20th-21st centuries; theory of art; philosophy of art; 1971-2023; 20.-21. století; katalogy výstav; eseje; sborníky; exhibition catalogs; essays; miscellanea; Ausstellungskatalog -- Městská knihovna -- 04.10.2023-28.01.2024 -- Prag